Association between ethnicity and thalassemia carrier status among secondary school students involved in thalassemia school screening programme in Pahang in 2016 - Rani, Nor Azila (2018)
Background: Thalassemia remains a public health concern in Malaysia despite screening programme has been conducted since 2004. Voluntary uptake towards screening test still unsatisfactory as there was lack of public awareness about the importance of screening activities. The public will not come forward for testing if they did not perceive they are susceptible to be a carrier. Multi-ethnicity population as in Pahang poses further challenges to overcome this situation. To our knowledge, there is yet no analytical study done looking at the association between carrier status with ethnicity in Malaysia. Objective: This study aimed to describe the different types of thalassemia carrier and to determine the association between ethnicity and thalassemia carrier status among secondary school students in Pahang. Methodology: A case control study was conducted from March 2018 till May 2018 involving ten districts in Pahang. The study used secondary data derived from ‘Rekod Saringan Talassemia Sekolah’ (KSK/ST/101/2016) form as the source of data. Cases were students who were diagnosed thalassemia carrier and controls were students who were not thalassemia carrier as documented in the database. Simple